Mecmû‘a - Muhammed b. Saîd el-Bûsîrî ([y.y.] [y.y.] [y.y.] [İstanbul])
1 mikrofilm makarasında 4 yazma eser (1. eser (89 poz : 87a vr.) ; 2. eser (poz 90-172 : 82a vr.) ; 3. eser (poz 173-215) : 4. eser (41b vr. ; poz 216-238 : 23a vr.)